Tinjauan Yuridis tentang Pengembalian Mahar Akibat Perceraian - Adiliah, Nur; Erlina; Nurjannah, St. (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to analyze the basic legal considerations of judges in judging the case of the return of dowry entirely due to divorce, as well as factors that cause the return of dowry. This study uses the method of library research by collecting data through quoting, adapting, and analyzing the contents of the literature relevant to the problems discussed. The results showed that in the decisions that were used as Case Studies, no judge decided to return the entire dowry given to the husband. This is in accordance with the provisions of Article 35 paragraph (1) KHI which requires the husband to pay half the dowry when mentalaq qabla al-dukhul. The factors that led to the return of the dowry are, among others, arranged marriages by families and disagreements. This research is broadly in accordance with the legislation in force in the religious courts.